DYNAMICS OF COMPETITIVE ACTIVITY INDICATORS OF QUALIFIED HANDBALL PLAYERS (Physical Culture and Sport: Scientific Perspective, 2025)
The article, based on the study of scientific literature, analyzes works on the competitive activity of qualified handball players. It is noted that competitive activity in handball encompasses a set of actions and interactions of players during official games aimed at achieving maximum results and team victory. For a detailed analysis of the indicators of the variable qualification activity of handball players, such aspects as technical and tactical actions, physical fitness, psychological stability, and game discipline should be taken into account.The following characteristics of competitive activity were identified: the volume of technical and tactical actions, the quality of performance of game actions (percentage of technical defects), the density of performance of technical and tactical actions (ratio of the number of technical and tactical actions to the time of participation in the game), the variability of technical and tactical actions (ratio of the total number of TTD to passes, dribbling, dribbling, interceptions, shots on goal). The need for a methodology for differentiated development of the physical qualities of qualified handball players, taking into account the individual profiles of their physical fitness and models of competitive activity and physical fitness of handball players of leading teams, is emphasized.Competitive activity indicators were determined by the total number of attacks; attack effectiveness; number of attacks against positional defense; attack effectiveness against positional defense; number of attacks on the move; attack effectiveness on the move; number of throws from the 6-meter zone; throws effectiveness from the 6-meter zone; number of throws from the 7-9m zone; throws effectiveness from the 7-9m zone; number of rebounds in attack; number of 7-meter free throws; 7-meter free throws made; number of missed goals; rebounds in defense; ball blocks; breakaway passes; total number of singles.It has been established that creating functional and technical-tactical prerequisites for performing a greater number of attacks on the move and their implementation by players of the Ukrainian national team is one of the real ways to increase the effectiveness of their competitive activities.The high level of preparedness of the rival teams at the European Championship, the lack of competition for the players of the two Ukrainian teams in the national championship, complicates the process of preparing for major European-level competitions.
Keywords: competitive activity; qualified handball players; dynamics of indicators; athletes